Efektivitas Unit Produksi sebagai Sumber Belajar Kewirausahaan di SMK Kota Yogyakarta - Yuliansah Yuliansah; Aliyah A. Rasyid (Faculty of Engineering, Universitas Negeri Yogyakarta, 2015)
The objective of this study was to determine how production units can be used effectively as an entreprenuership learning resource to increase the entrepreneurial learning motivation, to clarify the content of the entrepreneurial learning materials and to provide direct experiences for the Vocational High Schools students in Yogyakarta. This study is survey research with quantitative approach. The population of this study were 1.995 students of grade XI and grade XII at 17 Vocational High School in Yogyakarta. 333 students were selected as the sample. Questionnaires and documentation were used for collecting the data. The data was analysed through quantitative descriptive analysis using the Microsoft Excel software. The result of this study indicated that: (1) Production units were effective to increase the intrinsic entrepreneurial learning motivation of the students (2) Production units were ineffective to increase the extrinsic entrepreneurial learning motivation of the students (3) Production units were ineffective to clarify the entrepreneurial learning materials (4) Production units were ineffective to provide direct experiences for the students.